Uzbekistan : Modernizing Tertiary Education - World Bank (World Bank, Washington, DC, 2017)
Uzbekistan is a lower middle-income country located in Central Asia with a population of 30 million people and an economy that has been growing by over 8 percent per annum since the mid-2000s. The composition of the workforce has also changed dramatically in recent years. The higher education system is characterized by low access and concerns about the quality and relevance of the skills of its graduates. A recent regional skills study concluded that Uzbekistan is experiencing a substantial shortage of university graduates. The internal management of the higher education system is fragmented, with different actors having overlapping responsibilities, thereby making it difficult to ensure system-wide accountability. In order to enable the Uzbek higher education system to serve the economy and student population well, the quality assurance system should be compliant with global best practices while remaining locally relevant. While reported overall state budget spending on education, at around 8 percent of GDP, is one of the highest in the world, the share of this spending on tertiary education, at around 0.4 percent of GDP, is one the lowest. In summary, Uzbekistan’s higher education system needs to modernize to better adapt to needs of the country’s economy. The report, having analyzed the sector in detail, proposes measures to modernize the higher education sector in Uzbekistan.